Microbial diversity and biogeography across gastrointestinal tracts of Takifugu pufferfish revealed by full-length 16S amplicon sequencing - Xingkun Jin; Yan Shi; Zhenlong Sun; Yaohui Wang; Zhe Zhao (Water Biology and Security)
Fish, which are vital for both aquatic ecosystem functionality and global food supply, rely heavily on their gastrointestinal tract (GIT) microbiota for the digestion that underpins their growth and health. Takifugu pufferfish, which are an example of species evolved through adaptive radiation, possess a GIT that is specialized for antipredator defense and gluttonous feeding behaviors, offering a unique model to explore the effects of GIT compartmentalization and host genetics on gut microbial communities. Here we compiled 78 full and partial-length 16 ​S rRNA amplicon datasets across three anteroposteriorly distinct intestinal sites in a cohort of cohabitating artificial hybrid and purebred Takifugu pufferfishes. Our findings reveal a compositional and functional biogeography of pufferfish gut microbiota along the GIT and between host genetics. Additionally, the differential abundance of specific amplicon sequence variants and their correlation with host genetic backgrounds and intestinal sections highlight the role of environmental filtering in shaping microbial communities, with certain bacterial taxa exhibiting strong preferences for particular intestinal sites or genetic backgrounds, suggesting potential localized adaptation or functional specialization. This study enhances our understanding of the intricate interplay between host genetics, gut anatomy, and microbiota in fish, underscoring the importance of detailed microbial profiling in conservation efforts and aquaculture practices, and emphasizing the necessity of integrating full-length 16 ​S rRNA sequencing with partial-length datasets to comprehensively understand microbial diversity and function, paving the way for improved fish health management and sustainable aquaculture strategies.